The effect of incubation temperature and the starter CH1 in quality of yogurt produced from Cow's milk and Buffalo's milk - سلطانة, علي; حامد, فاتن; هوشة, ولاء (Latakia University Journal -Biological Sciences Series, 2021)
This study was carried out in cooperation between the Faculty of Agriculture at Tishreen University and the General Authority for Agricultural Scientific Research in Syria (GCSAR) at Al-Ghab Research Center during the year 2018-2019 with three replications of two types of milk, to study the effect of starter CH1 on the quality of milk made from cows and buffalo milk at incubation degrees (39-42-45)° and the analysis was performed at the Food Technology Laboratory at the Al-Ghab Research Center. The results of this study showed that the chemical composition was not affected by the addition of the starter. It also showed an improvement in the results of the sensory evaluation of processed milk at a mixing rate of 30% buffalo milk with 70% of cow's milk. Mixing ratios used at 42°.